An Approach to Performance Based Teacher Education - Henson, Kenneth T.; Indiana State Univ., Terre Haute. School of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
The experimental program in teacher education at Indiana State University was divided into four phases. Phase I, Course Introduction, pursued ideas of concept teaching, lesson plan formulation and lesson critiques. Phase II was devoted entirely to peer teaching. Prelesson planning and postlesson discussion augmented the one class hour each student had to teach in his specialty. Phase III was devoted to nonteaching skills, and Phase IV was aimed at nonteaching majors. In the future the program will continue operating as an experimental program. (JA)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Education Courses; Experimental Curriculum; Peer Teaching; Preservice Teacher Education; Teacher Education; Teacher Education Curriculum